ANALISIS POTENSI WISATA SITU CILEDUG DAN SITU GINTUNG DI KOTA TANGERANG SELATAN - Ferry Fauzi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
In the area of West Java, particularly in the area of South Tangerang, there is a natural or artificial lake with a small size in comparison to the lake known as Situ. In 2013, South Tangerang City there are nine pieces, four of which had almost lost or converted to residential areas. To develop situ in South Tangerang City into a tourist attraction water have to do with management and systematic program so that it can develop into a regional tourist mainstay. This study used survey methods, sampling points is determined by purposive sampling. Analysis was conducted on the water quality analysis, analysis of scoring to assess the quality of it, and Travel Compliance analysis. From the results of taking the measurements of water quality, the average quality of the water in Situ Gitung Ciledug and still comply with the quality standards based on Government Regulation No. 82 of 2001 on water quality management. Based on data from travel suitability index for fishing and boating between Situ Situ Gintung Ciledug and has a value equal weight, namely 81.48% and 94.12% second means it feasible to develop ecotourism activities such as fishing and boating.